The Impact of Artificial Intelligence (AI) on Human Resource Management Practices - Hendri Sucipto (Penelitian dan Pengembangan Ilmu, 2024)
This research discusses the impact of the integration of artificial intelligence (AI) in Human Resource Management (HRM) practices through a systematic literature review approach. Involving the analysis of 37 articles from various academic databases, the research identified the key benefits provided by AI in HRM, such as improved efficiency, process effectiveness and corporate decision making. However, significant challenges were also identified, including issues of data security, privacy and the need for HR skills development. In addition, the psychological impact on employees and work team dynamics is an important concern. In conclusion, the combination of AI in HRM has the capability to shape a new paradigm in human resource management, however it requires careful coping with rising demanding situations. This study offers a stable basis for a deep know-how of the complex interactions between AI and HRM, starting the door to in addition research and improvement on this region.